Implementasi Digital Marketing Tools Oleh Dwisapta Dalam Meningkatkan Brand Awareness Klien - Alifia Rasyida (PT. Hasba Edukasi Mandiri, 2025)
This report analyzes the implementation of digital marketing tools by DwiSapta in enhancing client brand awareness through content marketing strategies on social media. During the internship program, the author studied the application of various digital marketing tools such as Fanpage Karma, Meta Ad Library, and Google Analytics to support content strategy optimization on Instagram. The method used in this report is qualitative descriptive, including participatory observation and literature study. The observations indicate that digital marketing tools help improve brand awareness metrics such as engagement and reach. This report also provides recommendations for data-driven strategy development to support the sustainability of digital marketing campaigns.